Is God a person? Maimonides, Crescas, and beyond. (October 2022) - Lebens, Samuel
Abstract: Drawing from multiple generations of Jewish philosophy (from Maimonides until today), this article argues for the seemingly paradoxical conclusion that God is both fully, and not at all, a person. The apparent contradiction in this conclusion is resolved by appeal to a two-layered ontology.